2015
DOI: 10.1039/c4cs00244j
|View full text |Cite
|
Sign up to set email alerts
|

The reactivity of the active metal oxo and hydroxo intermediates and their implications in oxidations

Abstract: While the significance of the redox metal oxo moieties has been fully acknowledged in versatile oxidation processes, active metal hydroxo moieties are gradually realized to play the key roles in certain biological oxidation events, and their reactivity has also been evidenced by related biomimic models. However, compared with the metal oxo moieties, the significance of the metal hydroxo moieties has not been fully recognized, and their relationships in oxidations remain elusive until recently. This review summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
83
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(88 citation statements)
references
References 57 publications
5
83
0
Order By: Relevance
“…3). Therefore, we attempted to synthesize 2 through more standard methods for the synthesis of metal–oxo complexes using artificial oxidants, such as PhIO, peracids and hydroperoxides789101112. Interestingly, among the examined oxidants, we were able to obtain 2 with a significantly higher stability when PhIO was used as a terminal oxidant in the presence of a small amount of acid; the formation of 2 was not clean in the absence of acid due to the longer formation time and the less stability of 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3). Therefore, we attempted to synthesize 2 through more standard methods for the synthesis of metal–oxo complexes using artificial oxidants, such as PhIO, peracids and hydroperoxides789101112. Interestingly, among the examined oxidants, we were able to obtain 2 with a significantly higher stability when PhIO was used as a terminal oxidant in the presence of a small amount of acid; the formation of 2 was not clean in the absence of acid due to the longer formation time and the less stability of 2 .…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of the large KIE value and the good correlation between the reaction rate and BDEs of substrates, we conclude that hydrogen atom (H-atom) abstraction from the C–H bonds of the substrates by 2 is the rate-determining step (r.d.s.) in the C–H bond activation reactions789101112.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] Many examples of natural and synthetic terminal high-valent Fe-oxygen, and Mn-oxygen species have been reported in the last decade. 6,7 In sharp contrast, and despite some efforts, detection of terminal high-valent metal-oxygen species involved in the mode of action of highly efficient oxidation catalysts based on late-transition metals such as cobalt, nickel or copper are scarce. This is in part related to the "Oxo Wall" concept, which predicts that late transition elements cannot support a terminal oxido ligand in a tetragonal environment.…”
Section: Introductionmentioning
confidence: 99%
“…94,95 In particular, in collaboration with the Goldberg group we investigated the structure and reactivity of a manganese(V)-oxo corrolazine complex [Mn(O)(H 8 Cz)X], H 8 Cz is corrolazine without side chains and X is the axial ligand (X = no ligand or CN -/F -). We initially investigated the axial ligand effect on the dehydrogenation of 9,10-dihydroanthracene and showed that the reaction rate was enhanced by a factor of 2100 upon the addition of F -, while it increased by a factor of 16000 with addition of CN -.…”
Section: Spin-state Reactivity In Biomimetic Manganese(v)-oxo Complexesmentioning
confidence: 99%